Natural process-based coastal wetland restoration by relocating river flow paths in a river-dominated delta - Liehui Zhi; Dongdong Shao; Xu Xie; Xiaowen Li; Baoshan Cui; Junhong Bai (Communications Earth & Environment)
Abstract River flow path relocation primarily driven by socioeconomic goals has rarely been considered its potential ecological benefits as a natural process-based restoration strategy. We therefore proposed an integrated numerical simulation framework to simulate multiple natural processes in a river-dominated delta driven by flow path relocation scenarios, demonstrated by the case study in the Yellow River Delta. We found that intertidal wetlands initially formed and evolved into supratidal wetlands over time, and vegetation habitats emerged as an across-shore distribution of tidal wetlands. Reusing the historical river channel of the Diaokou achieved the best ecological benefits by accelerating sediment deposition and mitigating coastal wetland loss. Our research highlights the need to combine natural process-based and pattern-based restoration strategies. Understanding these processes is crucial for informing decision-makers about the long-term ecological and socioeconomic impacts on coastal wetlands, especially for those silt-rich and dynamically migrating rivers worldwide.